Gobioid fishes (Teleostei, Gobiiformes) of Penang Island, Malaysia: a comprehensive inventory with new records for Peninsular Malaysia - Tan, Yu Yang; Lavoué, Sébastien; Khaironizam, Md Zain (Zootaxa, 2026)
Penang Island in northern Peninsular Malaysia is undergoing rapid coastal development that threatens its intertidal and mangrove ecosystems, which support a high diversity of gobioid fishes. The only previous checklist for the island was published by Cantor in 1849, leaving major gaps in contemporary knowledge. This study provides an updated and comprehensive inventory of gobioid species based on surveys conducted across mudflats, brackish rivers, mangrove forests, and coastal marine habitats. A total of 46 species were collected, including 20 species newly recorded from Penang Island. Nine of these represent first records for Peninsular Malaysia and belong to the genera Eleotris, Butis, Favonigobius, Gobiopterus, Cryptocentrus, Mugilogobius, and Pseudogobius. When combined with Cantor’s account and other previous records, the gobioid fauna list of Penang Island comprises 61 species. This study highlights the substantial and previously undocumented diversity of gobioid fishes in the region and provides a foundation for future taxonomic, ecological, and conservation assessments.